COMMON FIXED POINT OF JUNGCK PICARD ITRATIVE FOR TWO WEAKLY COMPATIBLE SELF-MAPPINGS - Jamil, Zeana Zaki; Hussein, Zainab (Iraqi Journal of Science, 2021)
We develop the previously published results of Arab by using the function under certain conditions and using G-α-general admissible and triangular α-general admissible to prove coincidence fixed point and common fixed point theorems for two weakly compatible self –mappings in complete b-metric spaces.